Possible central nervous system oxygen toxicity seizures among US recreational air or enriched air nitrox open circuit diving fatalities 2004–2013 - Buzzacott, Peter; Denoble, P. (Informa UK Limited, 2017)
© 2017 Taylor & Francis Group, LLC. Background: The first diver certification programme for recreational ‘enriched air nitrox’ (EAN) diving was released in 1985. Concerns were expressed that many EAN divers might suffer central nervous system (CNS) oxygen toxicity seizures and drown. Methods: US fatalities on open-circuit scuba occurring between 2004–2013, where the breathing gas was either air or EAN, were identified. Causes of death and preceding circumstances were examined by a medical examiner experienced in diving autopsies. Case notes were searched for witnessed seizures at elevated partial pressures of oxygen. Results: The dataset comprised 344 air divers (86%) and 55 divers breathing EAN (14%). EAN divers’ fatal dives were deeper than air divers’ (28 msw vs 18 msw, p < 0.0001). Despite this, of the 249 cases where a cause of death was established, only three EAN divers were considered to have possibly died following CNS oxygen toxicity seizures at depth (ppO2 132, 142 and 193 kPa). Conclusion: The analysis of recreational diving fatalities in the US over 10 years found just one death likely from CNS oxygen toxicity among EAN divers. A further two possible, although unlikely, cases were also found. Fears of commonplace CNS oxygen toxicity seizures while EAN diving have not apparently been realized.